2020
DOI: 10.3390/su12198184
|View full text |Cite
|
Sign up to set email alerts
|

The “Green on Green” Conflict in Wind Energy Development: A Case Study of Environmentally Conscious Individuals in Oklahoma, USA

Abstract: Development in wind energy technology and deployment of infrastructure reduces reliance on fossil fuels and can further energy security goals. Wind energy, however, can conflict with other green interests. The goal of this research was to examine the perceptions of environmentally conscious individuals at the intersection of wind energy development and biodiversity conservation interests. A majority of respondents identified that they cared very much about both renewable energy development as well as biodivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…For example, in a study of residents living close to the Wolf Ridge wind farm in Texas, Swofford and Slattery [51] found that climate change concerns may influence support for wind power, albeit only to a limited extent. Burch et al [52] found similar results studying environmentally conscious people living in Oklahoma, USA. The participants claimed that they would oppose the local wind energy development if it negatively impacted biodiversity.…”
Section: Environmental Attitudesmentioning
confidence: 60%
See 2 more Smart Citations
“…For example, in a study of residents living close to the Wolf Ridge wind farm in Texas, Swofford and Slattery [51] found that climate change concerns may influence support for wind power, albeit only to a limited extent. Burch et al [52] found similar results studying environmentally conscious people living in Oklahoma, USA. The participants claimed that they would oppose the local wind energy development if it negatively impacted biodiversity.…”
Section: Environmental Attitudesmentioning
confidence: 60%
“…However, with the rise of offshore wind energy, more wind farms could be placed off the coast of major residential areas. However, Burch et al [52] found that 70% of environmentally conscious individuals in their study would support, to some extent, a hypothetical wind energy development near their place of residence. Environmentally conscious individuals hold strong environmental views that might change when facing a green-on-green conflict, such as wind energy [52].…”
Section: Vicinity Of Residence To the Wind Farmmentioning
confidence: 65%
See 1 more Smart Citation
“…Like conventional wind turbines, AWE systems will impact people and nature once deployed. Direct impacts could relate to the technology's sound emissions, visibility, and ecological effects, as indicated by research on wind turbines [2][3][4][5][6][7][8][9]. Potential acoustic impacts could result from noises emitted by the generator, winch, tether, and the flying kite.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study highlights how these factors are differentially linked to several scales of place by the words that are used on Instagram. This investigation is particularly relevant for visually focused social media platforms, such as Instagram, since a common criticism of RETs is their negative visual impact on the landscape [16]. This paper applies the sociocognitive approach (SCA) to the investigation of the language in Instagram posts.…”
Section: Introductionmentioning
confidence: 99%